Effects of prostate cancer and exercise training on left ventricular function and cardiac and skeletal muscle mass - Baumfalk, Dryden Ray (Kansas State University, 2018)
Prostate cancer is the most common type of non-skin cancer found in men and preliminary evidence suggests prostate cancer has atrophic effects on cardiac and left ventricle (LV) mass which are associated with reduced endurance exercise capacity in rats. Using a pre-clinical orthotopic model of prostate cancer, echocardiography was utilized to test the hypothesis that exercise training will mitigate prostate cancer induced-cardiac and skeletal muscle atrophy and improve LV function versus sedentary tumor-bearing counterparts. Methods: Dunning R-3327 AT-1 prostate cancer cells were injected orthotopically in male Copenhagen rats aged (n=39; ~5 mo. old). Animals were randomized into four groups, exercise-trained tumor-bearing (EXTB) or control (EXCON) and sedentary tumor-bearing (SEDTB), or control (SEDCON). Exercise training was performed via a rodent treadmill set at 15m/min with a 15° incline for 60 min/day for ~30 days. Animals underwent echocardiographic evaluation using the parasternal short axis view to examine ventricle dimensions pre-cancer or exercise (PRE) and 15 (Post 1) and 30 (Post 2) days post cancer cell injection and/or exercise training with tissues collected immediately after Post 2. Results: Cardiac and LV mass of SEDTB animals were significantly lower than all groups (p<0.05). Tumor mass was significantly negatively correlated with LV mass in EXTB (-0.75, p<0.02) and SEDTB animals (-0.72, p<0.02). EXCON group had significantly higher stroke volume Post 2 assessment compared to both sedentary groups (p<0.05), but not EXTB animals. Conclusion: The current investigation demonstrates prostate cancer independent of anti-cancer treatment significantly reduces cardiac mass, and LV mass as well as locomotor muscle masses. However, moderate intensity exercise training can mitigate cardiac and skeletal muscle atrophy with prostate cancer.
Keywords: Prostate cancer; Skeletal muscle; Cardiac muscle; Left ventricular function; Exercise training